(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Juan Francisco Sans (19602022), in addition to being an emblem to a generation of prolific composers, conductors, and musicologists, developed throughout his musical life the most essential and valuable virtue for the development of music in Venezuela: the constant art of selfsacrificing and guiding service towards his students and colleagues, through his empathetic, analytical and sensitive observation.